Developing and testing a theory based behavioural intervention in overweight and obese adults: The Healthy Eating and Active LifesTyle Health Intervention - Hattar, Anne (Curtin University, 2016)
This study tested the efficacy of the Healthy Eating and Active LifesTyle Health Intervention program, a 12-week randomised-controlled intervention based on social psychological theory aimed at promoting weight loss. Results revealed changes in dietary intake and physical activity, and related biomedical and psychological outcomes, over time, but no differences between the theory-based intervention conditions and a psycho-educational control conditions. Results also supported predictions of the psychological theories on which the intervention was based.